2005
DOI: 10.1021/jp053738h
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Effects on ESR and Optical Properties of Gold Atoms in γ Irradiated Organic Solid Solutions at 77 K

Abstract: Ligand effects on ESR and optical properties of Au0 atoms produced at 77 K in gamma irradiated solid solutions of AuCl/MTHF and AuCl/EtOH with and without HCl were investigated. Four groups of ESR lines were observed at 73 K more clearly around the magnetic fields at about 250, 280, 340, and 400 mT for both gamma irradiated MTHF and EtOH solid solutions with HCl than those without HCl. The values of a and g(J) calculated by Breit-Rabi analysis showed a remarkable dependence on the solvent polarity. It was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Additionally, there were Au(0) atoms that showed a hyperfine interaction with magnetic nuclei from the matrix. 162 By means of ENDOR spectroscopy, the properties of Cu 21 and (VO) 21 cations stabilised in polymers were investigated. It was found that the origin of the ENDOR signal is mainly due to anisotropic interactions between the unpaired spin and the nuclei of matrix atoms, such as water.…”
Section: Inorganic Radicalsmentioning
confidence: 99%
“…Additionally, there were Au(0) atoms that showed a hyperfine interaction with magnetic nuclei from the matrix. 162 By means of ENDOR spectroscopy, the properties of Cu 21 and (VO) 21 cations stabilised in polymers were investigated. It was found that the origin of the ENDOR signal is mainly due to anisotropic interactions between the unpaired spin and the nuclei of matrix atoms, such as water.…”
Section: Inorganic Radicalsmentioning
confidence: 99%
“…As a fundamental research to elucidate the function and effects of metal ions and/or atoms in biological systems, we have been investigating the ESR and optical properties of 1B metal atoms produced radiation-chemically by reducing their mono cations in solid solutions [4][5][6][7][8][9][10][11][12]. In the series of our previous studies, formation of metal atoms, Cu 0 , Ag 0 and Au 0 in irradiated solid solutions containing their mono cations were evidenced by ESR spectra that exhibited duplicate quartets [10], duplicate doublets [8] and quartet [12], respectively. The values of the hyperfine splitting, a and the gyromagnetic ratio for the electron shell, g J were evaluated from the Breit-Rabi equations that were applied for the case of isotropic forces of interaction between trapped atoms and ligands.…”
Section: Introductionmentioning
confidence: 99%